Defamation through Social Media: A Socio-Legal Study on the Effectiveness of Community-Based Countermeasures - Saragih, Fitrah Anata; Agusmidah, Agusmidah (Al-Qanun: Jurnal Kajian Sosial dan Hukum Islam, 2025)
Defamation is a violation that attacks a person's honor and image. In terms of legal sociology, this defamation case also needs to be used as well as using the theory of legal effectiveness in society, where to enforce the law not only law enforcement officers play an important role but also the community. As is the case when viewed from the study of the sociology of the law of defamation through social media, this is due to the culture of society that uses information and communication technology as a source of long-distance information and receives various information in seconds, so it is undeniable that with this development, various crimes will arise such as defamation through social media, as this act is also regulated in the ITE Law, namely Law Number 19 of 2016 concerning Law Number 11 of 2011, where there are rules regarding defamation through social media.